O papel da Fundação Parque Zoológico de São Paulo na conservação de espécies ameaçadas de extinção: o caso da Aburria jacutinga - Robbi, Beatriz (Universidade Federal de São Carlos, 2020)
The black-fronted piping guan, a Brazilian bird that inhabits the Atlantic Rainforest, is considered a great native seed disperser, it is currently classified as “Endangered” by the International Union of Conservation of Nature (IUCN) and Ministério do Meio Ambiente. As its behaviours are not widely studied yet, this research aims to contribute with behavioural knowledge about this species, which owns a conservation and reintroduction in wild program. The behaviours of black-fronted piping guan in captivity, at the São Paulo Zoo, were studied in four different phases: (1) when the individuals were apart in different enclosures, (2) during pairing period, (3) in the beginning of reproductive period and (4) in its peak, and with observations by the method Ad libitum and animal focal. The 86 identified behaviours were classified in 8 different categories. Our results indicate that the most reproduced behaviour by the black-fronted piping guan were “Stationary”, “Maintenance and Hygiene”, and “Locomotion”. The behavioural category’s frequencies did not have significant variation through the phases for the different individuals studied in function of the high variability of these frequencies observed for the different behaviours during the phases analysed. Regarding the reproductive behaviour, we verified an increase in the months August to November since this is the period of reproduction of this species. The two eggs laid in January might be an indication of reproductive period alteration of animals held in captivity. Environmental education and research are two of many fundamental points that are performed by modern zoos nowadays. Thereby, publicizing educational actions and research projects associated with fauna conservation on social media is something that can clarify to the public the real functions of a modern zoo. The weekly series with a total of 30 chapters nominated “De olho nas jacutingas” shared in the Fundação Parque Zoológico de São Paulo (FPZSP) social media (Facebook and Instagram) is an example of this: inspiring other professionals to do the same kind of divulgation and having a good acceptance of the public. An educational action was conducted with the FPZSP visitors, with the discussion of the importance of birds and biodiversity, the role of modern zoos and actions taken to the conservation of endangered species, as the black-fronted piping guan. The metrics analysed in this study were: reach, likes/reactions, sharings, visualizations, and comments. When we observe the number of likes and comments, the social network with the most involvement from their followers was Instagram, with a reach 3.3 times bigger than Facebook, demonstrating to be the best social media to publish conservation projects.
The role of Fundação Parque Zoológico de São Paulo in the conservation of threatened wildlife: the case of Aburria jacutinga
Keywords: Etograma; Comportamento reprodutivo; Manejo reprodutivo; Divulgação científica; Engajamento; Difusão; Ethogram; Reproductive behaviour; Reproductive handling; Scientific divulgation; Engagement; Difusion; CIENCIAS BIOLOGICAS::ZOOLOGIA; CIENCIAS BIOLOGICAS::ZOOLOGIA::COMPORTAMENTO ANIMAL